2021
DOI: 10.1111/ijcp.14209
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ experience, competence and perception of telepharmacy technology in response to COVID‐19

Abstract: Background: In the telepharmacy model, the pharmacist can play a pivotal role in delivering pharmaceutical services for patients. However, evidence of pharmacists' impact on improving patient outcomes through disease outbreak through telepharmacy is sparse.Objectives: This study aims to examine pharmacists' attitudes towards clinical benefits and identify challenges regarding the use of telepharmacy during the COVID-19 pandemic in Jordan. Method:A cross-sectional survey design was used to recruit eligible part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 30 publications
1
55
2
5
Order By: Relevance
“…This finding indicates that many community pharmacists are not ready to embrace new technology services such as telehealth. A cross-sectional survey study conducted in Jordan has shown that many pharmacists are doubtful to provide non-face-to-face services unless their healthcare outcomes become evident [38]. Another crosssectional study conducted in the Netherlands found very limited use of telehealth services in educating patients about COVID-19, and a very large proportion was hesitant in the provision of quality services through telecommunication for vulnerable people with health issues [39].…”
mentioning
confidence: 99%
“…This finding indicates that many community pharmacists are not ready to embrace new technology services such as telehealth. A cross-sectional survey study conducted in Jordan has shown that many pharmacists are doubtful to provide non-face-to-face services unless their healthcare outcomes become evident [38]. Another crosssectional study conducted in the Netherlands found very limited use of telehealth services in educating patients about COVID-19, and a very large proportion was hesitant in the provision of quality services through telecommunication for vulnerable people with health issues [39].…”
mentioning
confidence: 99%
“…Despite the reduction in face-to-face medical visits, patients report a good level of satisfaction, even greater than the health professionals [23]. The opportunity to implement telemedicine that has been provided by the SARS-CoV-2 pandemic is unique, and several considerations are mandatory to avoid failures, including integration of information systems, a multidisciplinary approach, and legal issues [24,25]. Telematic follow-up includes several options: phone call, video call, web-based platforms, email, or mobile apps [26].…”
Section: The Pandemic Accelerates the Digitalization Of Healthcarementioning
confidence: 99%
“…Researchers have highlighted that e-prescribing supports safe prescribing due to reductions in prescription error in some instances [24]; however, e-prescribing policies have often lagged behind what practice [25]; an The New Zealand Government required all visitors to the country to self-isolate for 14 days; public gatherings of more than 500 people restricted 19/03/2020 Borders and entry ports were closed to all non-residents (with some exceptions); indoor gatherings of more than 100 people restricted 21/03/2020 A newly minted four-level Alert system was introduced, to guide how individuals, businesses and the nation would operate at different levels of pandemic threat [9]; NZ set at Alert Level 2 23/03/2020 Moved up to Alert Level 3 (equivalent to a partial lockdown), schools closed, some other businesses were able to open, as long as there was no physical contact with customers; health services were to be delivered remotely as much as possible 25/03/2020 Moved up to Alert Level 4 (equivalent to a complete nationwide lockdown) during which people were told to stay at home and only essential businesses remained open, which included specified health services and community pharmacies. These were instructed to implement recognised COVID-19 infection control measures, which included hand washing/sanitising, physical distancing, replacing in-person visits with telehealth where possible, and cessation of some routine services [10] 27/04/2020 Moved down to Alert Level 3, allowing gatherings of 10 people, early childhood centres and some schools reopened 13/05/2020 Moved down to Alert Level 2, which maintained physical distancing and limits on size of gatherings but allowed all businesses and schools to re-open issue that has hampered efforts to introduce e-prescribing during the COVID-19 pandemic [26][27][28]. During the panedmic e-prescribing has been introduced in countries that had not previously used this approach, resulting in pharmacists calling for an extended scope of practice to better support the communities they work with [14].…”
mentioning
confidence: 99%
“…The majority of research exploring e-prescribing during the pandemic is contained within research and commentary on telemedicine and does not address e-prescribing directly [21][22][23][26][27][28][29][30][31].…”
mentioning
confidence: 99%
See 1 more Smart Citation